From ‘sugar daddies’ to ‘sugar babies’: exploring a pathway among age-disparate sexual relationships, condom use and adolescent pregnancy in South Africa - Toska, E.; Cluver, L.; Boyes, Mark; Pantelic, M.; Kuo, C. (C S I R O Publishing, 2015)
Background: Adolescent pregnancy has been linked to adverse outcomes. Most studies proposing risk pathways for adolescent pregnancy in South Africa are qualitative, hypothesising links among age-disparate relationships, reduced condom use and higher pregnancy rates. No known South African studies have quantitatively explored pathways to adolescent pregnancy. Objectives: This study aimed to: (i) identify the factors associated with adolescent pregnancy and (ii) explore a pathway of risk by assessing whether condom use mediated the relationship between age-disparate sexual relationships and adolescent pregnancy. Methods: A cross-sectional survey of 447 sexually active girls aged 10–19 years was undertaken in six health districts of South Africa. Multivariate logistic regressions controlled for confounders. Mediation tests used bootstrapping. Results: Consistent condom use (ß = –2.148, odds ratio (OR) = 8.566, P = 0.001) and school enrolment (ß = –1.600, OR = 0.202, P = 0.001) were associated with lower pregnancy rates. Age-disparate sex (ß = 1.093, OR = 2.982, P = 0.001) and long-term school absences (ß = 1.402, OR = 4.061, P = 0.001) were associated with higher pregnancy rates. The indirect effect of age-disparate sex on adolescent pregnancy through condom use was significant, irrespective of age, age at sexual initiation, poverty and residential environment (B = 0.4466, s.d. = 0.1303, confidence interval: 0.2323–0.7428). Conclusion: This survey supports hypotheses that inability to negotiate condom use in age-disparate sexual relationships may drive adolescent pregnancy. Interventions addressing these relationships, facilitating condom use and increasing access to sexual health services among adolescents might avert unwanted pregnancies.